Taḥlīl Nuṣūṣ Kitāb al-Lughah al-`Arabiyyah Li aṣ-Ṣaff aṡ-Ṡāni fi al-Marḥalah al-Mutawassiṭah (Dirāsah Taḥlīl al-Muḥtawā Min Ḥaiṡ al-Qawā`id an-Naḥwiyah) - Nisaul Fadhilatinur; Syarifuddin Syarifuddin (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
The book